Fair Price. Views on Royalties and Book Pricing in the Cultural Policy of Czechoslovakia in the 1950s and 1960s - Porizkova, Lenka (Bohemica Olomucensia, 2024)
Czechoslovakia in the 1950s and 1960s was controlled by the Communist Party, which strictly determined cultural policy. The book market was centrally planned and based on the reduction or negation of market mechanisms. In this study, I show the ways in which the Party in power tried to determine the optimal way of calculating authors' royalties in order to achieve a "fair" payment system and to limit "unearned" profit. Similarly, I examine what factors were taken into account in setting a uniform selling price for the book, which was not to be based on actual financial costs or the level of reader demand, but was to take into account the social value of the book and represent a "fair price for readers". Although the governing bodies of the Ministry of Culture tried to find a very precise and transparent way of calculating royalties and the selling price of a book, they had to gradually take into account more and more exceptions and specific circumstances relating to particular types of books or book genres. This demolished their ideas of a possible "ideal calculation" of a "fair price". The result was a system that had to be revised many times and was nearly never respected because of the number of exceptions. The study is based on research into archival material from the Ministry of Culture and demonstrates well the way in which literature and other book production was considered in the 1950s and 1960s. It shows how great discrepancy was generated between the utopian idea and its actual implementation in practice.
Keywords: authors' royalty; price of a book; Czechoslovakia; communism